2016
DOI: 10.3390/su9010032
|View full text |Cite
|
Sign up to set email alerts
|

An RVM-Based Model for Assessing the Failure Probability of Slopes along the Jinsha River, Close to the Wudongde Dam Site, China

Abstract: Abstract:Assessing the failure potential of slopes is of great significance for land use and management. The objective of this paper is to develop a novel model for evaluating the failure probability of slopes based on a relevance vector machine (RVM), with a special attention to the characteristics of failed slopes along the lower reaches of the Jinsha River, close to the Wudongde dam site. Seven parameters that influence the occurrence of landslides were selected as environmental factors; namely lithology, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The authors suggested the RVM equation developed might be utilized as an effective tool for predicting the status of epimetamorphic rock slopes. Li et al (2017) developed a novel model based on RVM for estimating the failure probability of slopes, with a focus to the characteristics of failed slopes along the lower reaches of the Jinsha River, close to the Wudongde dam site. The authors investigated seven criteria that influence the occurrence of landslides as environmental factors: lithology, b , H , slope aspect, slope structure, distance from faults, and land use.…”
Section: Application Of Gprmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested the RVM equation developed might be utilized as an effective tool for predicting the status of epimetamorphic rock slopes. Li et al (2017) developed a novel model based on RVM for estimating the failure probability of slopes, with a focus to the characteristics of failed slopes along the lower reaches of the Jinsha River, close to the Wudongde dam site. The authors investigated seven criteria that influence the occurrence of landslides as environmental factors: lithology, b , H , slope aspect, slope structure, distance from faults, and land use.…”
Section: Application Of Gprmentioning
confidence: 99%
“…where s is the kernel parameter. This function is not affected by outliers, and it can handle nonlinear relationships between class labels and characteristics (Li et al, 2017). SVM/SVR is one of the most extensively used regression-based ML methods for detecting decision boundaries and separating various groups (Li and Dong, 2012;Samui, 2013).…”
Section: Brief Overview Of Different Ai Techniquesmentioning
confidence: 99%
“…(b) It is common that there are correlations between product attributes and between requirements; e.g., the shell material is correlated to the weight of smartphones. This reality against the pre-assumption of mutually independent between attributes for some intelligent classifiers, e.g., NB (Li et al 2016;Wang and Tseng 2015). (c) Without the Bayesian framework, intelligent classifiers only provide the value of class, i.e., the class in which an individual belongs (Read et al 2011).…”
Section: Feasible Configurationsmentioning
confidence: 99%
“…Relevant vector machine (RVM) is a probability model based on sparse Bayesian learning theory. Under a conditional distribution and the associated maximum likelihood estimation, the nonlinear problems in low-dimensional space are transformed into linear problems in high-dimensional space by kernel functions [17][18][19][20]. RVM has the advantages of good learning ability and strong generalization ability, provided that a suitable kernel function is selected and the hyper-parameters are set correctly.…”
Section: Introductionmentioning
confidence: 99%
“…RVM has the advantages of good learning ability and strong generalization ability, provided that a suitable kernel function is selected and the hyper-parameters are set correctly. The method of RVM has been widely used in academia to deal with geotechnical problems, such as slope stability and reliability analysis [17][18][19][20][21][22], the ultimate capacity of driven piles [23], and seismic liquefaction predictions [23,24]. In previous studies, the method of RVM is combined with global optimization algorithms to build the optimal models in a wide study from predicting geotechnical parameters, self-compacting concrete parameters [25][26][27][28][29], to estimating oil price and river water levels [30,31].…”
Section: Introductionmentioning
confidence: 99%